Biodiversity of Oak (Quercus leucotrichophora) Dominated Forest Stands in Mussoorie Garhwal Himalaya, Uttarakhand, India - Prerna; Sanjay Singh (The Bioscan, 2025)
This paper presents the initial phase of developing the Malaysia Counsellor Performance Indicator (M-CPI), a new assessment tool designed to evaluate counsellor performance. Employing a mixed-method research design, the study commenced with a needs analysis conducted through an online survey, which garnered responses from 102 participants. Additionally, semi-structured interviews were conducted with nine (9) participants to identify essential components of the M-CPI. The analysis revealed eight critical domains of counsellor performance: (i) knowledge (theoretical and knowledge transfer), (ii) skills (case management, practical skills, and academic/professional writing), (iii) interpersonal relationships and interaction, (iv) cultural and religiosity, (v) professional roles and expertise, (vi) ethics and legality, (vii) attitudes and personality, and (viii) referral practices. The findings underscore the multifaceted nature of counselling competencies, laying the groundwork for the M-CPI and enhancing the assessment of counsellor performance in Malaysia.